Challenges and Needs of Professional Development for Lecturers of English-medium Instruction - Coffin, Prarthana (Connexion: Journal of Humanities and Social Sciences, 2014)
There is an increased use of English as the medium of instruction at the higher educational level in Southeast Asia countries in response to the enactment of an ASEAN Economic Community policy in 2015. Using English-medium instruction is an obvious choice of a university to achieve a prominent status in the international community. As a result, supporting the use of English as the medium of instruction can enhance the expansion of the internationalization process of a university and a country. There is no doubt that the challenges of becoming an English- medium university are tremendous. These papers gives insights into challenges occurring from the contextual factors and further supports that there is a need to develop a systematic professional development program for the English-medium instruction lecturers. Therefore, the paper aims to answer the following questions: (1) What are the contextual factors that should be addressed as challenges in becoming an English- medium university? (2) How can those challenges turn into incentives in developing an effective English-medium instruction status? (3) In which ways can a systematic professional development program contribute to the quality of English medium instruction lecturers?